(untitled) (Journal of Ideas in Health, 2024)
The COVID-19 pandemic, caused by the novel SARS-CoV-2 coronavirus, has had an unprecedented global impact, highlighting the urgent need to understand the virus’s penetration mechanisms, prevention methods, and the most effective treatment strategies. This review aims to provide a comprehensive overview of the current knowledge and emerging developments in these areas. Firstly, the review examines the intricate pathways through which SARS-CoV-2 penetrates host cells. It explores the viral entry receptors, including angiotensin-converting enzyme 2 (ACE2), and highlights the potential involvement of other receptors. Additionally, the review delves into the processes of viral replication, shedding light on the viral kinetics and factors influencing transmissibility. Secondly, the review presents an in-depth analysis of the various measures employed to protect individuals and communities from SARS-CoV-2 infection. It discusses the effectiveness of non-pharmaceutical interventions, such as physical distancing, mask-wearing, and hand hygiene, in reducing transmission. Furthermore, the review explores the development and deployment of vaccines, including traditional approaches and novel vaccine platforms, examining their efficacy, safety, and the challenges posed by emerging variants. Lastly, the review provides an overview of the current treatment strategies for COVID-19. It evaluates the effectiveness of antiviral drugs, immunomodulatory therapies, and supportive care approaches in managing the disease. By gaining a deeper understanding of these aspects, we can contribute to the development of evidence-based interventions and improve global health outcomes in the face of COVID-19 and future pandemics.